HIV risk screening for high-yield community testing services for orphans and vulnerable children: a literature review. Issue 2 (3rd April 2018) - Duffy, Malia; Sharer, Melissa; Berhan, Aida; Kose, Judith; Cornman, Helen; Pearson, Jennifer; Eagan, Sabrina
ABSTRACT: This systematic literature review focuses on the identification of risk and protective factors – sociodemographic, behavioral and structural – associated with orphans' and vulnerable children's (OVC) likelihood of being or becoming HIV infected to inform the development of a high-yield community screening tool to identify at-risk OVC and link them to HIV testing services. The review examines the state of the evidence regarding HIV risk, protective factors and screening for HIV testing, including algorithms used in OVC and youth community and clinical program settings to identify those already infected with HIV and those at risk of acquiring HIV. A total of 26 studies were found eligible for abstraction, encompassing 428, 501 participants. The literature is sparse and inadequate related to screens for HIV testing among OVC, and only seven distinct screens were identified. Overall, it is clear that it is critical to identify children and youth most at risk of being HIV positive in community settings, while being mindful of risks associated with stigma and discrimination. Identifying these children and youth is critical to reaching the first and second UNAIDS targets – 90% of people living with HIV diagnosed and 90% of those with diagnosed HIV infection on treatment – and ultimately achieving viral suppression, leading to an AIDS-free generation.